Making sense with numbers. Unravelling ethico‐psychological subjects in practices of self‐quantification. (10th October 2019) - Pols, Jeannette; Willems, Dick; Aanestad, Margunn
Abstract: Prevention enthusiasts show great optimism about the potential of health apps to modify peoples' lifestyles through the tracking and quantification of behaviours and bodily signs. Critical sociologists warn for the disciplining effects of self‐tracking. In this paper we use an empirical ethics approach to study the characteristics and strivings of the various types of 'ethico‐psychological subjects' that emerge in practices of self‐quantification by analysing how people and numbers relate in three cases of self‐quantification: in prevention discourse, in testimonies from the quantified self (QS) movement and in empirical work we did with people with Diabetes type I and with 'every day self‐trackers'. We show that a free subject that needs support to enact its will is crucial to understand the optimism about prevention. In the QS‐movement the concern is with a lack of objective and personalised knowledge about imperceptible processes in the body. These subjects are decentered and multiplied when we trace how numbers in their turn act to make sense of people in our empirical study. We conclude that there are many different types of ethico‐psychological subjects in practices of self‐tracking that need to be explored in order to establish what good these practices of self‐quantification might do.